Determination of vapour–liquid equilibria diagram structure of five-component monoazeotropic system - L. A. Serafimov; A. V. Frolkova; G. A. Syomin (Тонкие химические технологии)
In this paper algorithm of determination of vapour-liquid equilibria diagram structure for five-component system with and without five-component azeotrope was described. This algorithm allows determining existence, sign of Poincare index and type of five-component azeotrope using principle of azeptropy. One model and one real (acetone–methanol–methyl acetate–ethyl acetate–water) system was analyzed with this algorithm.